Pelatihan Pengembangan Modul Ajar Kurikulum Merdeka - Bahar, Erni Ekafitria; Nursakiah; Sitti Rahma Tahir; Ikhbariaty Kautsar Qadry; Takdirmin; Abd. Kadir Jaelani (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The Merdeka Curriculum teaching module development training aims to equip educators with comprehensive knowledge, skills, and understanding of the concepts, principles, and practical steps in developing effective and innovative teaching modules, which are expected to contribute significantly to improving the overall quality of education. The activity was conducted in three stages: preparation, implementation, and evaluation. The preparation phase involved preparing administration, materials, and other necessary equipment. The implementation phase consisted of three sessions: an initial questionnaire, material presentation and Q&A session, and a final questionnaire after the activity. The evaluation phase involved participant feedback on the activity. The training took place at the UPTD of SMPN 2 Bontonompo and was attended by 15 teachers. The results of this series of activities concluded that: (1) training participants had a good understanding of the components and principles of developing Merdeka Curriculum teaching modules; (2) There was an increase in participants' understanding of creating Merdeka Curriculum teaching modules after the training; (3) Participants responded positively to the training, with 73.3% finding it very beneficial, and 80% responding that their competency had improved significantly after participating.